Menuntut Kelengkapan Peran Media: Tidak Hanya Membawa Tetapi Juga Membongkar Pencitraan - Effendi Ghazali (Jurnal Ilmu Sosial dan Ilmu Politik, 2011)
In the midst of direct election of public officials era (in Indonesia was marked by legislative elections/ includes regional representatives, election of president and vice president in 2004 and local elections since 1st June 2005), modern political communication relies heavily on the media to carry the political messages, mainly advertisements regarding themselves and the candidate program. The question then, when the media in Indonesia began to complement their roles, in accordance with the flow of media performance, media responsibility, media accountability, to the concept of role in the democratization of media (Media for Democracy monitor). With a starting point on these concepts, this paper tries to take some cases and the phenomenon as a discussion of earlier atempts to highlight how the media do its part in full and should be systematic.